Ecosystem changes after Early Cretaceous seawater intrusion into the proto-South Atlantic Ocean - Jian Ma; Leonardo F. Cury; Anelize M. B. Rumbelsperger; Heidi L. Albrecht; Erwin W. Adams; Joachim E. Amthor; Xingqian Cui; Antoine Crémière; Kei Sato; Kristin D. Bergmann; Roger E. Summons (Communications Earth & Environment)
Abstract The early evolution of the South Atlantic Ocean following the Cretaceous break-up of Gondwana is extensively recorded in rift basins along the conjugate margins of Africa and Brazil. For the Brazil side, divergent views of the source and pathway of the initial seawater incursion persist due to a paucity of recognized transitional sequences that document marine transgressive deposits over the continental interior. To address this, we conducted a high-resolution sedimentological and geochemical study through a core in the Campos Basin that encompasses the key lithologic switch from lacustrine carbonate to marine evaporite settings. Steroid lipid biomarkers, derived from pelagophyte marine algae, make a striking appearance in concert with a pronounced negative shift of 87Sr/86Sr ratios and coincident with the appearance of anhydrite. Importantly, the sulfur-sequestered biomarkers reveal a dynamic system where redox-stratified and anoxic conditions were amplified along with a deepening chemocline through the marine transition.